Experimental studies on AA6063-Cu dissimilar friction stir welding using Inconel 601 tool. (2020) - Sahu, Santosh Kumar; Haldar, Nimai; Datta, Saurav; Kumar, Rajneesh
Abstract: AA6063-Cu dissimilar friction-stir welding was performed in the present work. Owing to excellent high temperature strength, and adequate wear resistance, nickel based super alloy Inconel 601 was used as FSW tool. Two weld specimens were prepared at constant tool rotational speed but varied weld speed, and tool offset distance. Microstructural characteristics along with mechanical properties of the welded specimen including tensile strength, and micro-indentation hardness were studied. Intermetallic compounds were found to be formed at the weld interfacial region. Lamellar intercalated microstructure with predominant flow pattern was observed in the stirred zone. Dispersed copper (layered or bulk) was observed over aluminium matrix. Distribution of copper and aluminium over the weld surface as well as interfacial region was studied through Electron Probe Micro Analyser (EPMA). Maximum tensile strength attained ∼103 MPa, corresponded to the weld specimen obtained at tool rotation = 1120 RPM, weld speed = 100 mm/min, and tool offset = 0.95 mm. Fractographic analysis of the same specimen revealed brittle fracture mechanism with predominant cleavage planes. Moreover, micro-hardness profile was found highly influenced by the formation of hard intermetallic layers.